Explanations of Institutional Change: Reflecting on a “Missing Diagonal” - Johannes Gerschewski (American Political Science Review, 2021)
Previous research on institutional change has concentrated on two types of explanations. On one hand, the dualism of path dependency and critical junctures has advanced our understanding of how institutional change occurs due to sudden exogenous shocks. On the other hand, more recent critiques have established a better understanding of endogenous, gradual change. This article is motivated by observations that current research tends to overlook what I call the “missing diagonal.” I argue that we need to disentangle the sources of a cause (exogenous vs. endogenous) from its time horizon (sudden vs. gradual). By cross-tabulating these two dimensions, the proposed typology of institutional change explanations is able to capture complex multilayered as well as sequential arguments of institutional change. The typology urges scholars to be more precise with their social science language of erosion and decay, while serving as a generator for an innovative research agenda on endogenous ruptures.
Keywords: 300; institutional change; sociological theory; typology; cause; path dependence